Coporate branding and consumers on social media - Araujo, Theo, ....- (Amsterdam : SWOCC, 2018)
Social media plays an increasingly crucial role in brand communication. The importance of social media goes beyond product brands: it is also relevant to how companies execute their corporate branding strategies, and communicate their brand portfolio online. This research report aims to extend our knowledge about how companies can leverage their corporate brand in product brand communication on social media. Looking specifically at consumer-related activities, it reviews what companies and consumers currently do on social media platforms when it comes to discussing the corporate brand in the context of product brand communication, and identifies the key decsisions that companies should consider when setting up or reassessing their social media activities to leverage the corporate brand.
Keywords: Social media ; Consumenten; Social media ; Merken